Superhydrophobic modification of cellulose sponge fabricated from discarded jute bags for oil water separation. Issue 2 (April 2021) - Ahuja, Dheeraj; Dhiman, Shiva; Rattan, Gaurav; Monga, Sheetal; Singhal, Sonal; Kaushik, Anupama
Abstract: Recent oil spills endanger the aquatic ecosystem besides huge loss of natural resources, hence require immediate attention. To develop economical solution for combating oil spills, discarded jute bags, with 60–65% cellulose were used to fabricate cellulose sponge using sol-gel method followed by freeze drying. The sponge surface was rendered superhydrophobic by dip coating with Tetraethyl-orthosilicate/Hexadecyltrimethoxy Silane (TEOS/HDTMS). The pristine and dip coated hydrophobic cellulose sponge (DHCS) were characterized for structure, morphology and hydrophobicity. FE-SEM confirmed the hydrophobic coating of TEOS/HDTMS on sponge surface, while superhydrophobicity was established with static contact angle of 151°. DHCS exhibited oil water separation efficiency of 98.5% and 97.2% and equilibrium adsorption efficiency of 35.55 g/g and 31.37 g/g for diesel oil and motor oil, respectively. The adsorption follow pseudo-second order kinetics with regression coefficients, R 2 > 0.99. Equilibrium studies indicated that the Freundlich isotherm was best fit isotherm for oil water removal by DHCS. DHCS displayed significant recyclability with slight reduction of adsorption capacity to 85.2% for diesel oil and 82.5% for motor oil of its initial value after 10 cycles. Graphical Abstract: ga1 Highlights: Cellulose nanofibrils were isolated from discarded jute gunny bags. Cellulose sponges were fabricated utilizing sol-gel technique followed by freeze drying. Cellulose sponges were Dip coated using TEOS/HDTMS for superhydrophobicity. Contact angle of 151° confirmed super hydrophobicity of the sponge. Developed sponges were explored for oil water separation.